Pengaruh Kemudahan Penggunaan Aplikasi Access by KAI terhadap Kepuasan Pelanggan Kereta Api Pariaman Ekspres - Silvia, Silvia; Putri, Sinta Westika (Lembaga Yasin AlSys, 2025)
This study is motivated by the suboptimal customer satisfaction in using the Access by KAI application for the Pariaman Express train service, which is presumed to be influenced by ease of use. The research aims to determine the effect of ease of use on customer satisfaction. A quantitative associative research design was employed, involving 98 respondents determined using the Slovin formula. Data were collected through a four-point Likert scale questionnaire, which was tested for validity and reliability using SPSS 26.0. The ease-of-use variable was measured based on five indicators from Quesenbery (2004), while customer satisfaction was measured based on three indicators from Indrasari (2019). Simple linear regression analysis shows that ease of use has a positive and significant effect on customer satisfaction, with the regression model Y = 9.444 + 0.485X. The coefficient of determination (R²) of 0.641 indicates that 64.1% of the variation in customer satisfaction is explained by the ease of use of the application, while the remainder is influenced by other factors. In conclusion, the higher the ease of use of the Access by KAI application, the higher the customer satisfaction with the Pariaman Express train service.